THE EFFECTS OF COMMUNICATION, WORK ENVIRONMENT AND WORK DISCIPLINE ON THE PERFORMANCE OF VILLAGE OFFICERS IN KROYA SUB-DISTRICT CILACAP REGENCY - Hermin Endratno; Fahmi Afrizal (Universitas Muhammadiyah Metro Lampung, 2020)
The purpose of this study is to examine the effect of communication, work environment and work discipline on the performance of village officers in Kroya District, Cilacap Regency. The sampling technique in this study was done by purposive sampling method. Multiple regression analysis was used to analyze the data. The results of the analysis indicate that the variables of communication, work environment and work discipline significantly affect the performance of village officers in the Kroya Sub-district, Cilacap Regency.Keywords: Communication, Work Environment, Work Discipline, Performance